Fluid-dynamic design and characterization of a mini-ORC turbine for laboratory experiments. (September 2017) - Pini, M.; De Servi, C.; Burigana, M.; Bahamonde, S.; Rubino, A.; Vitale, S.; Colonna, P.
Abstract: High temperature Organic Rankine Cycles power systems of low power capacity, i.e. 3-50 kWe, are receiving recognition for distributed and mobile energy generation applications. For this type of power plants, it is customary to adopt a radial-turbine as prime mover, essentially for their ability to cope with very large volumetric flow ratio with limited fluid-dynamic penalty. To date, the design of such turbines is based on design guidelines and loss models developed mainly for turbo-chargers, subsequently adapted by means of non-validated computational fluid-dynamic calculations. In the attempt to provide data sets for CFD validation and calibration of loss models, a mini-ORC radial inflow turbine delivering 10kW of mechanical power will be realized and tested in the Propulsion and Power Laboratory of TU-Delft. The fluid dynamic design and characterization of the machine is detailed in this paper. According to available models, the results indicate that the optimal layout of mini-ORC turbines can substantially differ from that of radial-inflow turbines utilized in more traditional applications, strengthening the need of experimental campaigns to support the conception of new design practices.